(3GSGSjGJ GdJaGVd h GdJcGeds - (3bJMj Ndjd(B, (3MeOGfs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2008)
(3LGA gPG GdcJGH aj SJ hMOGJ JfGhd ef NdGdgG CSGSjGJ GdJaGVd hGdJcGed cGdGbJQGfGJ hGdfgGjGJ hJYQja GdeTJbI hbhGYO GdGTJbGb , hdJbQjH gPg GdCehQ ef Pgf GdWGdH bOe GdcJGH JWHjbGJ aj GdJaGVd eKd GdeYGOdGJ GdeQJHWI HGdRef hGdJRGjO hGdJfGbV hef Ke YQV ddJcGed hJWHjbGJg cGdJcGed ZjQ GdeMOhO hJcGed GdGbJQGfGJ , hGdcKjQ ef GdYfGhjf hGdeSGFd GdJj JSGYO Ydi JfTjW GdPgf hage GdeGOI s
Keywords: (3JMdjd QjGVjs; (3JaGVds; (3JcGeds